Relationship of Economic Growth with Tourism Sector - Holik, Abdul (Universitas Negeri Semarang, 2016)
This research aims to analyze the impact of foreign tourists towards the economic growth. It was conducted from 1995 until 2012 on five ASEAN member countrie: Indonesia, Malaysia, Thailand, Philippines, and Singapore. It used the quantitative method; it is one-way random effect of panel regression. The data, which is functioned as dependent variables, were taken from WDI (World Development Indicator) of the World Bank for the Gross Domestic Product (GDP). Meanwhile, the data of revenue from the foreign tourist visit (Rec), the number of foreign tourist arrival (Arr), and the exchange rate (Xrate) are functioned as the independent variables. Based on the research result, there is evidence that international tourism can increase the economic growth in those countries. The three independent variables have a positive and significant impact to the dependent variables. Based on the findings, the governments of five ASEAN member countries should be able to maintain the sustainability of tourism sector in order to be stronger and to have global market-orientation. In fact, tourism services can support the economic growth because the potential of those ASEAN countries cannot be taken lightly.